Baltijos šalių istorijos bibliografija seniau ir dabar - Kaegbein, Paul (Knygotyra, 2003)
In the article based on the paper presented at the conference "Erfahrungen und Perspektiven der bibliographischen Arbeit für Ostmitteleuropa" (The experience and perspectives of the bibliographic work in East Central Europe) in the Herder Institute (Marburg, Germany), 14 March, 2003, the author reviews the state-of-the-art of the bibliography of history in Estonia, Latvia, and Lithuania. In a short overview of the state history, the attention is paid to a late statehood of the countries in this region and the earlier dependence on different states. Till the end of the 18th century, Estonia and Latvia were under the political influence of Germany, Lithuania – of Poland. The cultural influence was significant during later periods.Further, the author analyses regional bibliographies compiled in the Baltic states and other countries published after 1990 that he knows. He divides those into current and retrospective publications. The author covers the bibliographies of regional and Lithuanian history as well as general bibliographies of Estonian and Latvian publications in foreign languages and also a bibliography of Lithuanian periodicals.Herder Institute in Marburg cooperates with Polish, Czech, and Slovakian bibliographers and creates a bibliographic database of the history of Central East Europe on the Internet. The creators also plan to include the bibliographic data on the history of the Baltic states.